Complementary and alternative medicine use and cost in functional bowel disorders: A six month prospective study in a large HMO - Drossman Douglas A; Turner Marsha J; Feld Andrew D; Levy Rona L; Palsson Olafur S; van Tilburg Miranda AL; Whitehead William E (BMC, 2008)
Abstract Background Functional Bowel Disorders (FBD) are chronic disorders that are difficult to treat and manage. Many patients and doctors are dissatisfied with the level of improvement in symptoms that can be achieved with standard medical care which may lead them to seek alternatives for care. There are currently no data on the types of Complementary and Alternative Medicine (CAM) used for FBDs other than Irritable Bowel Syndrome (IBS), or on the economic costs of CAM treatments. The aim of this study is to determine prevalence, types and costs of CAM in IBS, functional diarrhea, functional constipation, and functional abdominal pain. Methods 1012 Patients with FBD were recruited through a health care maintenance organization and followed for 6 months. Questionnaires were used to ascertain: Utilization and expenditures on CAM, symptom severity (IBS-SS), quality of life (IBS-QoL), psychological distress (BSI) and perceived treatment effectiveness. Costs for conventional medical care were extracted from administrative claims. Results CAM was used by 35% of patients, at a median yearly cost of $200. The most common CAM types were ginger, massage therapy and yoga. CAM use was associated with female gender, higher education, and anxiety. Satisfaction with physician care and perceived effectiveness of prescription medication were not associated with CAM use. Physician referral to a CAM provider was uncommon but the majority of patients receiving this recommendation followed their physician's advice. Conclusion CAM is used by one-third of FBD patients. CAM use does not seem to be driven by dissatisfaction with conventional care. Physicians should discuss CAM use and effectiveness with their patients and refer patients if appropriate.